Personalized‐induced neural stem cell therapy: Generation, transplant, and safety in a large animal model. Issue 1 (15th July 2020) - Bomba, Hunter N.; Sheets, Kevin T.; Valdivia, Alain; Khagi, Simon; Ruterbories, Laura; Mariani, Christopher L.; Borst, Luke B.; Tokarz, Debra A.; Hingtgen, Shawn D.
Abstract: In this study, we take an important step toward clinical translation by generating the first canine‐induced neural stem cells (iNSCs). We explore key aspects of scale‐up, persistence, and safety of personalized iNSC therapy in autologous canine surgery models. iNSCs are a promising new approach to treat aggressive cancers of the brain, including the deadly glioblastoma. Created by direct transdifferentiation of fibroblasts, iNSCs are known to migrate through the brain, track down invasive cancer foci, and deliver anticancer payloads that significantly reduce tumor burden and extend survival of tumor‐bearing mice. Here, skin biopsies were collected from canines and converted into the first personalized canine iNSCs engineered to carry TNFα‐related apoptosis‐inducing ligand (TRAIL) and thymidine kinase (TK), as well as magnetic resonance imaging (MRI) contrast agents for in vivo tracking. Time‐lapse analysis showed canine iNSCs efficiently migrate to human tumor cells, and cell viability assays showed both TRAIL and TK monotherapy markedly reduced tumor growth. Using intraoperative navigation and two delivery methods to closely mimic human therapy, canines received autologous iNSCs either within postsurgical cavities in a biocompatible matrix or via a catheter placed in the lateral ventricle. Both strategies were well tolerated, and serial MRI showed hypointense regions at the implant sites that remained stable through 86 days postimplant. Serial fluid sample testing following iNSC delivery showed the bimodal personalized therapy was well tolerated, with no iNSC‐induced abnormal tissue pathology. Overall, this study lays an important foundation as this promising personalized cell therapy advances toward human patient testing.